Analisis Profil dan Faktor-Faktor yang Memengaruhi Perilaku Kepatuhan Pengobatan untuk Pasien Diabetes Mellitus Lanjut Usia - Makkulawu, Andi; Setiadi, Adji Prayitno; Rahardjo, Tri Budi Wahyuni; Setiawan, Eko (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2019)
Adherence with medication is one of the important factors in controlling blood glucose levels in patients with diabetes mellitus (DM), which in turn also determines the risk of diabetic complications. The profile and factors that influence adherence behaviour in the use of medication in elderly diabetic patients in Indonesia, especially in East Surabaya, are not yet known. The purpose of this study was to identify profiles and factors that influence the behavior of drug use adherence in elderly DM patients. A cross-sectional study was conducted in 32 Karang Werda or support groups for elderly in East Surabaya. Identification of the respondent’s level of adherence was carried out using the Adherence to Refill and Medication Scale (ARMS) questionnaire while the contributing factors towards adherence behaviour were identified using a published questionnaire. Both questionnaires have been validated in elderly people living in Surabaya. Result of adherence profile analysis was expressed in terms of percentage while determinant factors analysis was identified by using the highest mean among 14 sub-domains included in the questionnaire. In total, 281 elderly diabetic patients were recruited in this study. It was identified that 67.26% of the respondents were classified as non-adherence patients. The dominant factors that contribute to the behavior of medication adherence in elderly diabetic patients were social support, product-related factors, health workers, and emotional factors. Appropriate interventions to optimize the use of medications in elderly diabetic patients need to be identified and implemented according to the identified contributing factors.